IMPLIKASI HUKUM TERHADAP PRODUSEN DITINJAU DARI SEGI INDIKASI GEOGRAFIS - Darmayanti, Ni Komang Putu Sri; Danyathi, Ayu Putu Laksmi (Kertha Negara : Journal Ilmu Hukum, 2023)
The purpose of this research is to determine the process of registering geographical indications (GI) or a number of superior products as intellectual property rights, and to find out the legal implications of geographical indications after the enactment of the work copyright law. This research uses normative legal research methods, namely research that refers to the laws and regulations that apply well in Indonesia. This research can also be said as library research. With the results of research for the certification process for Geographical Indications (GI), the Government of the Republic of Indonesia has issued Government Regulation (PP) Number 51 of 2007 concerning Geographical Indications. The Government Regulation regulates the Registration of Products or Goods that have certain characteristics so that they are eligible to be registered as Geographical Indications (GI). Judging from the substantive changes in the article between the Trademark Law and Geographical Indications and the Job Creation Act, according to the author, there is no indication of a regulation that is detrimental to the public interest regarding changes to the trademark rules because the changes tend to make it easier for people who want to apply for registration of their business marks.